2015
DOI: 10.1016/j.healun.2015.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of lung transplant recipients with telomerase mutations

Abstract: Background Successful lung transplantation (LT) for patients with pulmonary fibrosis from telomerase mutations is limited by systemic complications of telomerase dysfunction including myelosuppression, cirrhosis, and malignancy. We describe clinical outcomes among 14 LT recipients with telomerase mutations. Methods Subjects underwent LT between February 2005 and April 2014 at 5 LT centers. We abstracted data from medical records, focusing on outcomes reflecting post-LT treatment effects likely to be complica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
2
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(88 citation statements)
references
References 29 publications
4
68
2
4
Order By: Relevance
“…Over 50% of affected individuals had a diagnosis other than IPF. Other studies of ILD patients with short telomere lengths have also found high percentages of non-IPF diagnoses, including hypersensitivity pneumonitis, unclassified interstitial pneumonia and combined pulmonary fibrosis and emphysema [30, 31]. We found discordant diagnoses among affected individuals with the same inherited rare mutation in 80% of kindreds.…”
Section: Discussionsupporting
confidence: 58%
“…Over 50% of affected individuals had a diagnosis other than IPF. Other studies of ILD patients with short telomere lengths have also found high percentages of non-IPF diagnoses, including hypersensitivity pneumonitis, unclassified interstitial pneumonia and combined pulmonary fibrosis and emphysema [30, 31]. We found discordant diagnoses among affected individuals with the same inherited rare mutation in 80% of kindreds.…”
Section: Discussionsupporting
confidence: 58%
“…Thrombocytopenia and a need for platelet transfusion were frequent, and myelodysplastic syndrome and/or bone-marrow failure occurred in some patients. Acute kidney failure requiring dialysis support seemed unexpectedly frequent in two series (0-50%) [58][59][60]. The prevalence of infections and acute/chronic rejections did not differ from historical data, but there was no control group.…”
Section: Pulmonary Involvementmentioning
confidence: 80%
“…Three retrospective series recently reported the outcome of lung transplantation in 26 patients with TERT and TERC mutations [58][59][60]. Almost all patients required adjustment of immunosuppression because of haematological toxicity.…”
Section: Pulmonary Involvementmentioning
confidence: 99%
“…Sequencing of telomere-related genes was not systematically performed. Five subjects with telomere-related gene mutations (all with telomere lengths <10 th percentile) were included in other studies(8, 11). …”
Section: Methodsmentioning
confidence: 99%
“…Heterozygous mutations in these genes are associated with short telomere lengths and a rapidly-progressive form of pulmonary fibrosis, which is most commonly characterized as idiopathic pulmonary fibrosis (IPF)(8). Small observational studies have found that pulmonary fibrosis patients with TERT or TERC mutations have high rates of bone marrow failure, infection, renal dysfunction, and allograft dysfunction after lung transplant(911). However, these studies were limited by small numbers of patients and the absence of a comparison cohort.…”
Section: Introductionmentioning
confidence: 99%